Psoriasis comorbidity management in the COVID era: a pressing challenge - Song, Yang; Yao, Lei; Li, Shanshan; Zhou, Junfeng (Frontiers in Microbiology, 2023)
The global COVID-19 pandemic has presented a significant, ongoing challenge since its emergence in late 2019. Today, the Omicron strain, which is less lethal but more contagious than the original outbreak strain, continues to pose substantial health risks. In this background, the management of psoriatic comorbidities has become even more complex, particularly for patients with underlying inflammatory, metabolic, or cardiovascular diseases. This review aims to summarize current research on comorbid COVID-19 and psoriasis, and provide insights into the development of evidence-based management strategies. By providing appropriate patient instruction, implementing protective measures, and re-evaluating medication prescriptions based on each patient’s unique situation, healthcare professionals can effectively address the challenges faced by patients with comorbid psoriasis in the COVID-19 era.